(untitled) (Nepal Journal of Epidemiology, 2021)
Background: Dengue virus (DENV) continues to be an epidemic with high mortality rates. The clinical features, especially in the early phase of infection, are nonspecific and there is no single marker that can be reliably deployed for diagnostics. Further, serotype and genotype diversity is not clearly understood. This study was conceived to understand the performance characteristics of various diagnostic markers; serotype and genotype distribution is thus a vital requirement. Methods: A subset of blood samples was obtained for all the clinically suspected Dengue cases during the period January to December 2017. The samples were tested for IgM and IgG antibodies and NS1 antigen by both ELISA and rapid tests. Real-time PCR, Conventional PCR and sequencing was performed based on the serology results. Correlation of the data with demographic and clinical details was used to analyze the performance characteristics of various tests. Results: Clinical signs and symptoms could not predict dengue positivity due to lack of specific symptoms. The performance of IgM rapid test was found to be lower than the ELISA method (53.5% agreement). The NS1 rapid and NS1 ELISA tests were comparable (89.2% agreement). Majority of the infections were caused due to DEN-2 serotype and phylogenetic analysis revealed all the sequenced DEN-2 serotypes belong to Genotype IV. Three sequences with were deposited into NCBI GenBank (GenBank accession number MW583116, MW579054 and MW579053). Conclusion: Our comprehensive data suggests that NS1 ELISA and PCR are best used in the early phase of dengue infection (< 5 days post-onset of fever), whereas IgM antibody detection is reliable only in the late phase. We also highlight the unreliable performance of rapid tests.